Comparative Analysis of the SMART and MFEP Methods for Selecting Baking Ingredient Suppliers for Bakery MSMEs in East Bekasi District - Elvi Fetrina; Ikaningrum Nurazizah; Mohammad Al-Habsie (PT. Tech Cart Press, 2026)
The selection of raw material suppliers is one of the key factors in maintaining product quality and operational efficiency for Micro, Small, and Medium Enterprises (MSMEs) in the bakery industry. Supplier selection processes that are still conducted subjectively have the potential to cause problems such as inconsistent material quality, delayed deliveries, and increased operational costs. This study aims to analyze and compare the performance of the Simple Multi-Attribute Rating Technique (SMART) and the Multifactor Evaluation Process (MFEP) methods in supporting decision-making for the selection of baking ingredient suppliers for bakery MSMEs in East Bekasi District. The research employed a comparative quantitative approach, with data collected through observations, interviews, and questionnaires administered to five bakery MSME owners. The evaluation was based on five main criteria: base price, material quality, delivery timeliness, service quality, and payment term flexibility. The collected data were then processed using the SMART and MFEP methods to generate preference scores and supplier rankings. The results indicate that both methods consistently identified the best supplier, namely alternative S1, with a SMART score of 0.845 and an MFEP score of 8.25. Differences in ranking were found among the middle alternatives, indicating variations in the sensitivity of the calculations between the two methods. The SMART method produced rankings that were more responsive to changes in criterion weights due to its linear utility approach, whereas the MFEP method tended to provide more stable results through direct weighted factor evaluation. Based on these findings, the SMART method is more suitable for dynamic supply chain environments, while the MFEP method is better applied in relatively stable and standardized evaluation conditions.